Efficacy of Intralesional Triamcinolone Acetonide for the Treatement of Chalazaion - Waqar-ul-Huda, Tanweer Hassan Khan, Shakir Zafar (Pakistan Journal of Ophthalmology, 2017)
Purpose: To assess the Resolution of Chalazion after intralesional injection of Triamcinolone Acetonide at tertiary care hospital in Karachi. Study Design: Case series. Place and Duration of study: LRBT free tertiary eye care hospital Karachi from January 2016 to June 2016. Material and Methods: A case series was done in 62 eyes of 62 patients using intralesional injection of triamcinolone acetonide in patients of chalazion. The patients included in the case series were those who had chalazion and presented to outpatient department from January 2016 to June 2016. The patients were included using non-probability purposive sampling technique. The size of the chalazion was measured by using measurement rings of different sizes. Resolution of chalazion after intralesional injection of triamcinolone acetonide at 2 weeks was noted. Data analysis was done using SPSS version 13.0. Results: Fifty (80.6%) patients showed complete resolution of the lesion with single injection of triamcinolone acetonide. Complete resolution of chalazion after treatment was directly associated with the duration of chalazion. With longer duration of the lesion complete resolution of the lesion decreased. Conclusion: Intralesional triamcinolone acetonide injection is very useful in resolving chalazion of different sizes, so this treatment can be used as a convenient treatment option for chalazion. Keywords: Chalazion, Intralesional, Triamcinolone acetonide